Differentially expressed genes identified through RNA-seq with extreme values of principal components for beef fatty acid in Nelore cattle - Olivieri, Bianca Ferreira [UNESP]; Braz, Camila Urbano [UNESP]; Brito Lopes, Fernando [UNESP]; Peripolli, Elisa [UNESP]; Medeiros de Oliveira Silva, Rafael; Ruegger Pereira da Silva Corte, Rosana; Albuquerque, Lucia Galvão de [UNESP]; Pereira, Angélica Simone Cravo; Stafuzza, Nedenia Bonvino; Baldi, Fernando [UNESP] (Wiley, 2020)
The aim of this study was to identify differentially expressed genes (DEG) in the Longissimus thoracis muscle of Nelore cattle related to fatty acid (FA) profile through RNA sequencing and principal component analysis (PCA). Two groups of 10 animals each were selected containing PC1 and PC2 extreme DEG values (HIGH × LOW) for each FA group. The intramuscular fat (IMF) was compared between cluster groups by ANOVA, and only the sum of monounsaturated FA (MUFA) and ω3 showed significant differences (p <.05). Interestingly, the highest percentage (95%) of phenotypic variation explained by the sum of the first two PC was observed for ω3, which also displayed the lowest number of DEG (n = 1). The lowest percentage (59%) was observed for MUFA, which also revealed the largest number of DEG (n = 66). Since only MUFA and ω3 exhibited significant differences between cluster groups, we can conclude that the differences observed for the remaining groups are not due to the percentage of IMF. Several genes that have been previously associated with meat quality and FA traits were identified as DEG in this study. The functional analysis revealed one KEGG pathway and eight GO terms as significant (p <.05), in which we highlighted the purine metabolism, glycolytic process, adenosine triphosphate binding and bone development. These results strongly contribute to the knowledge of the biological mechanisms involved in meat FA profile of Nelore cattle.
Keywords: beef cattle; lipids; metabolic pathways; RNA sequencing